Elimination of Australian epidemic strain (AES1) pseudomonas aeruginosa in a pediatric cystic fibrosis center. Issue 11 (12th October 2018) - Kevat, Ajay; Carzino, Rosemary; Massie, John; Harrison, Jo; Griffiths, Amanda L.
Abstract: Introduction: In this cohort study spanning an 18‐year period, we evaluated the prevalence and associated mortality rate of epidemic strains of pseudomonas aeruginosa (PsA), especially Australian Epidemic Strain Type 1 (AES1), in a pediatric cystic fibrosis center practicing cohort segregation and early PsA eradication. Methods: Cohort segregation was introduced in January 2000. PsA clonal strain was determined by pulse‐field‐gel‐electrophoresis (PFGE) at the time of routine collection of airway specimens. Children with PsA underwent eradication treatment with anti‐pseudomonal antibiotics over 2‐3 months. We analyzed changes in prevalence and mortality from 1999 to 2016. Results: The prevalence of AES1 declined from 69 (20%) in 1999 to 16 (5.4%) in 2006, to 1 (0.4%) in 2016. The prevalence of PsA overall diminished less over the same period, from 128 (37%) patients in 1999 to 57 (23%) in 2016. New acquisition of AES1 became less common over time, with no new cases identified from 2011. Those who contracted AES1 had a greater risk of death than those who did not (Odds Ratio 4.9, 95%CI 2.5‐9.6). Patients with other AES PsA types were uncommon (AES2 n  = 5, AES5 n  = 2, AES14 n  = 3, AES19 n  = 1). Conclusions: Cohort segregation was associated with reduction in AES1 prevalence ascertained by PFGE surveillance for patients in a single large pediatric cystic fibrosis center. Other alterations in practice such as early eradication treatment may also have contributed to reduced PsA prevalence. These factors combined with the transition of chronically infected patients over time to adult centers has eliminated AES1 from our clinic, with an accompanying mortality decrease.